Experimental and numerical investigation on the mode I and mode II interlaminar fracture toughness of nitrogen-doped reduced graphene oxide reinforced composites - Soyugüzel, Tahir; Mecitoğlu, Zahit; Kaftelen-Odabaşı, Hülya (Elsevier B.V., 2023)
An experimental and computational study is carried out to investigate the toughening effect of nitrogen-doped reduced graphene-oxide particles (ND-RGOP) in mode I and mode II delamination of carbon fiber/epoxy laminates. For mode I, both delamination initiation and propagation toughness are enhanced by 126.3% and 119.3% with 0.8 ND-RGOP addition. In addition to mode I toughness enhancement, ND-RGOP reinforcement also increases mode II toughness. The highest mode II delamination toughness value was obtained in 0.4ND-RGOP laminates with an increase of 45.6% compared to neat laminates. However, as seen in the bending tests, the maximum force of the end notch bending (ENF) specimens with 0.8 ND-RGOP added is not lower than that of neat laminates. The interlaminar fracture toughness is high due to the rough path of delamination with ND-RGOP addition, which is also observed by FESEM images of the delamination surfaces. In addition to the experiments, a cohesive zone model with parametric traction stress value was prepared in ABAQUS/CAE to obtain the critical traction stresses in the delamination of laminates. The critical normal traction stress of double cantilever beam (DCB) specimens is increased by over 20% with the addition of ND-RGOP. Besides, the critical interlaminar shear stress in mode II delamination for ENF samples is significantly improved. © 2023 Elsevier Ltd
Keywords: Carbon fiber reinforced polymers; Cohesive zone model; Delamination; Fracture toughness; Reduced graphene-oxide